Hubungan di antara Orientasi Pembelajaran Matematik (OPM) dengan pencapaian matematik - Veloo, Arsaythamby (Universiti Sains Malaysia Press, 2010)
The purpose of this study was to identify the relationship between Study Orientation in Mathematics (SOM) and mathematics achievement.In addition, this study also aimed to identify the SOM variable which is the best predictor of mathematics achievement.The respondents of the study were 674 students from 16 public secondary schools in Kedah that were selected using stratified random sampling.The Mathematics multiple-choice test comprises 40 items which has five items (12.50%) for Numbers area, nine items (22.50%) for Shapes area and 26 items (65%) for Relationship area.The SOM questionnaire consists of 72 items and the following five variables: attitude, anxiety, habit, problem solving behaviour and study milieu in learning Mathematics.The pearson correlation and multiple regression were used for significance tests.The findings of the study showed that attitude, habit, problem solving behaviour and study milieu in learning Mathematics have positive relationship whereas anxiety in learning Mathematics has negative relationships with mathematics achievement.The findings also showed that attitude was the best predictors of mathematics achievement.The proposed ARoS Model emphasizes the importance of assessing student’s affective attributes before assessing their cognitive ability and this indirectly will improve their mathematics achievement.There for, SOM can be used by teachers, counsellors and principals to assess students’ affective attributes in identifying students’ cognitive ability in learning Mathematics.